Bridging Aging and Intellectual/Developmental Disabilities in Research, Policy, and Practice. Issue 1 (4th January 2019) - Heller, Tamar
Abstract: Bridging the fields of aging and intellectual/developmental disabilities (I/DD) in research, policy, and practice can improve the lives of people both in aging with I/DD and in older adults aging into disabilities. These two groups have both unique and common needs for health and long‐term services and supports. Examples of bridging include exchange of research, adaptation of interventions, and development of policy embracing ideas from both fields. Research exchange includes scoping reviews of health promotion and family caregiving interventions in aging and I/DD. Adaptations from aging include chronic disease self‐management, falls prevention programs, dementia caregiving, retirement planning, and end‐of‐life care. The Administration on Community Living programs in the United States are examples of policy initiatives that bridge aging and disabilities. Opportunities for bridging the fields of aging and I/DD exist, and there are numerous examples of productive practice. Moving forward, it is important to consider the influence of future developments, such as technology and universal design, on the bridging movement. Further research can benefit our understanding of how to improve the bridge between these fields to an even greater extent.